Umkehr Ozone Profile Analysis and Satellite Validation - Balis, Dimitris S.; Koukouli, MariLiza; Fountoukidis, Panagiotis; Fragkos, Konstantinos; Miyagawa, Koj; Petropavlovskikh, Irina; Garane, Katerina; Bais, Alkiviadis F. (My University, 2024)
High quality and vertical resolution profiles of ozone that cover the troposphere, UTLS and the stratosphere, have been obtained by Brewer and Dobson spectrophotometers in a special viewing mode called Umkehr. Within the second phase of the European Space Agency IDEAS+ framework further efforts have been made to improve the operational Umkehr analysis algorithm and provide homogenized dataset optimized for the validation of the ozone profile observations by space-born sensors such as S5P/TROPOMI and GOME2 on the MetOp platforms. Within this phase of the project the improved Umkehr retrieval methods have been applied to Umkehr ozone profile measurements for a total of 9 ground-based stations (4 Brewer and 5 Dobson), and we updated the timeseries of the ground-based stations until the end of 2022. In the following sections, the Umkehr observations retrieval methodology and the new improvements are briefly described. The particular settings used in each type of instrument, Brewer and Dobson so as to perform Umkehr measurements are given, and the homogenization methodology of the measurements is separately described, with emphasis on the recent activities related to the Arosa Dobson record. The results section comprises of the final updated time series of Umkehr observations for 4 Brewer and 5 Dobson stations, the description of the validation methodology, and the comparisons of the optimized Umkehr profiles to GOME-2 and TROPOMI satellite measurements. Case studies for Thessaloniki, Greece, Hradec Kralove (Czech Republic) (Brewer), Lauder, New Zealand and Boulder USA (Dobson) are shown, while a detailed summary of the validation statistics are presented for all stations and 4 atmospheric layers.